STRATEGI KOMUNIKASI EFEKTIF PUBLIC RELATIONS DALAM BRANDING TERHADAP PELAYANAN PRIMA DI KANTOR KECAMATAN KOTABUMI LAMPUNG UTARA - Sasfira, Rima; Monica, Della (Komsospol, 2022)
This article explores effective public relations communication strategies in branding excellent service at the North Lampung Kotabumi District Office, using a qualitative approach. This research aims to understand how effective communication carried out by public relations can influence public perceptions of the quality of service in the office. Involving in-depth interviews, observation and documentation this research highlights the importance of positive communicative interactions to strengthen the image of excellent service and brand. The research results show that implementing targeted communication strategies can increase public satisfaction, create a positive image, and build loyalty towards public services. Using qualitative methods, this research provides an in-depth understanding of the dynamics of communication at the Kotabumi District Office, as well as providing a basis for recommending improvements to more effective communication strategies. This research can provide guidance for local governments in improving excellent service branding at the local level.